Blind’s Slide Creator - Razan Onab; Nabeel Zanabeet (My University, 2024)
One of the most valuable skills that any graduated student should master is public speaking & presentation production, it would be great whenever you use high technical software to generate and to present your slides, that provides a prop to communicate with audience and a clear understanding of your idea. What if a blind person intends to make his own slide! So here comes the idea of this project, is to implement a smart web application (Blind’s Slide Creator) that manage and guide blind people to create slides of their own whenever they want, all of this is through a complete voice system. The website will guide him through the whole process, he will have a wide choice of voice commands to manipulate the slides keeping the procedure simple and easy, after that a PowerPoint presentation will be downloaded automatically, next he will be able to start his own show enhanced by also voice instruction to notify him with the alive changes occur on the screen through the presentation.